A Development of Questionnaire for Assessing Implementation 0f Multicultural Education In Learning at Elementary School - Lalu Hamdian Affandi (Jurnal Pendidikan Humaniora, 2017)
Abstract: The aim of this research is to develop a questionnaire of multicultural education implementation in learning at elementary schools. As a preliminary study, this research target is to identify a factor(s) underlying questionnaire items. Questionnaire was developed based on four of five dimension of multicultural education proposed by James Banks in four point Likert Scale. Data were collected from 150 elementary school teachers employed in Lombok, West Nusa Tenggara. In order to achieve above goal, exploratory factor analysis was conducted through maximum likelihood method with promax extraction procedure. Eigenvalues greater than 1 and scree test were used to retain a factor(s) underlying items construct. Whereas Cronbach’s alpha is used to determine questionnaires reliability. This research found that from 54 items, there are 29 items valid for 6 factors of multicultural education dimensions with item load 0.40 or larger and 0.878 Cronbach’s alpha. These 6 factors are critical thinking practices for student, opportunity for student to reduces prejudice, cultural diversity as a learning resource, equality in learning opportunity, teacher’s knowledge about students’ cultural background, and encouragement for students learning initiatives. Based on this result, researcher suggests for further research to clarify and test those six factors by engaging larger sample size.Key Words: assessment of multicultural education implementation, elementary school Abstrak: Tujuan dari penelitian ini adalah untuk mengembangkan kuesioner implementasi pendidikan multikultural dalam pembelajaran di sekolah dasar. Sebagai studi pendahuluan, sasaran penelitian ini adalah untuk mengidentifikasi faktor-faktor yang mendasari butir kuesioner. Kuesioner dikembangkan berdasarkan empat dari lima dimensi pendidikan multikultural yang diajukan oleh James Banks dalam empat titik Skala Likert. Data dikumpulkan dari 150 guru sekolah dasar di Lombok, Nusa Tenggara Barat. Untuk mencapai tujuan di atas, analisis faktor eksploratori dilakukan melalui metode maximum likelihood dengan prosedur ekstraksi promax. Eigenvalues lebih besar dari 1 dan scree test digunakan untuk mempertahankan butir yang mendasari item construct. Sedangkan alpha Cronbach digunakan untuk menentukan reliabilitas kuesioner. Penelitian ini menemukan bahwa dari 54 item, ada 29 item yang valid untuk 6 faktor dimensi pendidikan multikultural dengan item load 0,40 atau lebih besar dan 0,878 alpha Cronbach. Keenam faktor ini adalah praktik berpikir kritis bagi siswa, kesempatan bagi siswa untuk mengurangi prasangka, keragaman budaya sebagai sumber belajar, persamaan dalam kesempatan belajar, pengetahuan guru tentang latar belakang siswa, dan dorongan untuk inisiatif belajar siswa. Berdasarkan hasil penelitian ini, peneliti menyarankan untuk penelitian lebih lanjut untuk mengklarifikasi dan menguji keenam faktor tersebut dengan melibatkan ukuran sampel yang lebih besar.Kata kunci: penilaian pelaksanaan pendidikan multikultural, sekolah dasar